PEMUTUSAN SEMENTARA HUBUNGAN BILATERAL ANTARA INDONESIA-AUSTRALIA TERKAIT PENYADAPAN OLEH PEMERINTAH AUSTRALIA DITINJAU DARI HUKUM INTERNASIONAL - Situmorang, Ridho Fauzi; Indra, Mexsasai; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Indonesia-Australia relationship has existed since the beginning of the independence of Indonesia. Australia is one country that gives political support to the struggle of the people and the nation of Indonesia in achieving independence. In the implementation of foreign relations possible actions or circumstances are contrary to or inconsistent with foreign policy, national legislation and international law and practice. Action and such circumstances should be avoided According to the constitution and international law.The act of espionage obtain information prohibited under international law, because they can interfere with the sovereignty and security of the State Recipient In accordance with the above description, the writer interested to do research with the title Termination While Bilateral Relations Between Indonesia-Australia Related Tapping By Australian Government Seen From the International Law. Then to determine whether termination while Indonesia-Australia bilateral relationship is right or espionage cases related to wiretapping under international law and the latter are the implications of bilateral interim termination of the Indonesia-Australia ties. Results of the discussion in this paper is, international law regards action the Australian government wiretapping is not illegal. But in particular the tapping action has hurt the provisions of the Treaty of Lombok. The impact of these intercepts is reduced confidence in the Government of Indonesia to the Australian Government, while the termination of the cooperation in the field of intelligence and the military until the completion of the tapping issue is clearly not just the negative impact of this wiretapping issue, but there were also the positive impact that pushed the two countries, namely Indonesia and Australia to develop a code of conduct together in conducting international relations ensure legal certainty from any action outside of the code of conduct.Kata Kunci: Pemutusan sementara, hubungan bilateral antara Indonesia- Australia, terkait enyadapan